DEVELOPMENT OF A MATURITY MODEL FOR TELEMEDICINE - Van Dyk, L.; Schutte, C.S.L. (The South African Journal of Industrial Engineering, 2011)
ENGLISH ABSTRACT: For more than a decade, the South African National Department of Health (DoH) has recognised the potential benefit of information and communication technology (ICT) in the delivery of health care to rural areas. Despite generous funding and proven technology, not many telemedicine systems have proved sustainable after the pilot phase. The purpose of this paper is to develop a maturity model that can be implemented to measure and manage the capability of a health system, for use in the delivery of sustainable health care after the pilot phase of a telemedicine project. The validity of the telemedicine maturity model (TMMM) is tested within the context of the South African public health sector. AFRIKAANSE OPSOMMING: Die Suid Afrikaanse Nasionale Departement van Gesondheid het reeds meer as n dekade gelede die voordeel besef wat inligtings- en kommunikasietegnologie kan bied ten opsigte van die lewering van gesondheidsorg in afgele gebiede. Ten spyte van ruim befondsing en bewese tegnologie, is daar egter min volgehoue telegeneeskundedienste in die publieke gesondheidstelsel van Suid Afrika. Die doel van hierdie artikel is om n volwassenheids-model te ontwikkel wat gebruik kan word om die vermovan n gesondheidstelsel te bepaal en bestuur, ten einde telegeneeskunde loodsprojekte vol te hou. Die geldigheid van hierdie telegeneeskunde volwassenheidsmodel (TMMM) is getoets binne konteks van die publieke gesondheidsektor van Suid Afrika.